Unusually wide co-factor tolerance in a metalloenzyme; divalent metal ions modulate endo–exonuclease activity in T5 exonuclease - Garforth, Scott J. (Oxford University Press, 2001)
T5 5′–3′ exonuclease is a member of a homologous group of 5′ nucleases which require divalent metal co-factors. Structural and biochemical studies suggest that single-stranded DNA substrates thread through a helical arch or hole in the protein, thus bringing the phosphodiester backbone into close proximity with the active site metal co-factors. In addition to the expected use of Mg(2+), Mn(2+) and Co(2+) as co-factors, we found that divalent zinc, iron, nickel and copper ions also supported catalysis. Such a range of co-factor utilisation is unusual in a single enzyme. Some co-factors such as Mn(2+) stimulated the cleavage of double-stranded closed-circular plasmid DNA. Such endonucleolytic cleavage of circular double-stranded DNA cannot be readily explained by the threading model proposed for the cleavage of substrates with free 5′-ends as the hole observed in the crystal structure of T5 exonuclease is too small to permit the passage of double-stranded DNA. We suggest that such a substrate may gain access to the active site of the enzyme by a process which does not involve threading.